Using Surface Acoustic Wave Devices for Self-powered Sensing & Interaction - Swaminathan, Sai Ganesh; Hudson, Scott; Hodges, Steve (SelfSustainableCHI Workshop, CHI 2020, 2020)
In this paper, we introduce surface acoustic wave (SAW) devices for self-powered sensing and interaction. We report on the general working principles of SAW devices, and their capability to be used as passive sensors and to operate wirelessly. We also present existing methods to manufacture SAW devices. We then provide the results of our early experiments using SAW devices for a novel sensing application and we introduce a new approach for low-cost fabrication of custom SAW devices. Finally, we present future directions for this work and its potential application in ubiquitous computing and HCI.